Alternative Treatments for Indoor Residual Spraying for Malaria Control in a Village with Pyrethroid- and DDT-Resistant Vectors in The Gambia - Tangena, Julie-Anne A.; Adiamoh, Majidah; D’Alessandro, Umberto; Jarju, Lamin; Jawara, Musa; Jeffries, David; Malik, Naiela; Nwakanma, Davis; Kaur, Harparkash; Takken, Willem; Lindsay, Steve W.; Pinder, Margaret (PLOS ONE, 2013)
BackgroundMalaria vector control is threatened by resistance to pyrethroids, the only class of insecticides used for treating bed nets. The second major vector control method is indoor residual spraying with pyrethroids or the organochloride DDT. However, resistance to pyrethroids frequently confers resistance to DDT. Therefore, alternative insecticides are urgently needed. Methodology/Principal FindingsInsecticide resistance and the efficacy of indoor residual spraying with different insecticides was determined in a Gambian village. Resistance of local vectors to pyrethroids and DDT was high (31% and 46% mortality, respectively) while resistance to bendiocarb and pirimiphos methyl was low (88% and 100% mortality, respectively). The vectors were predominantly Anopheles gambiae s.s. with 94% of them having the putative resistant genotype kdr 1014F. Four groups of eight residential compounds were each sprayed with either (1) bendiocarb, a carbamate, (2) DDT, an organochlorine, (3) microencapsulated pirimiphos methyl, an organophosphate, or (4) left unsprayed. All insecticides tested showed high residual activity up to five months after application. Mosquito house entry, estimated by light traps, was similar in all houses with metal roofs, but was significantly less in IRS houses with thatched roofs (p=0.02). Residents participating in focus group discussions indicated that IRS was considered a necessary nuisance and also may decrease the use of long-lasting insecticidal nets. Conclusion/SignificanceBendiocarb and microencapsulated pirimiphos methyl are viable alternatives for indoor residual spraying where resistance to pyrethroids and DDT is high and may assist in the management of pyrethroid resistance.